Use of prescription medication prior to suicide in Norway - Anne Reneflot; Silje L. Kaspersen; Lars Johan Hauge; Jorid Kalseth (BMC, 2019)
Abstract Background The use of psychotropic medications in relation to mental disorders is considered central to preventing suicide. However, few studies have addressed prescription patterns at different time points within the last year prior to suicide and compared these with those of the general population. Methods We use data covering the period from 2010 to 2011 from the Norwegian Cause of Death Registry and the Norwegian Prescription Database to examine dispensing patterns of prescription medication within 12 months and within 30 days of suicide. Our data includes all registered suicides in Norway among individuals aged 15 years and older in 2011 (n = 594), 434 men and 160 women. Dispensing of prescription medication in the general population (n ≈ 4 million) are used for comparison. Results Dispensing of any prescription medication were high and varied from 95.6% for females and 83.2% for males within 12 months of suicide, to 64.4% for females and 47.2% for males within 30 days of suicide, respectively. The percentages with dispensed prescription medication increased with age. A similar sex and age pattern was observed for the dispensing of psychotropic medications. Within the last 30 days, close to one in two were dispensed psychotropic medications. The dispensing of antidepressants, hypnotics and sedatives was more common than the dispensing of other categories of psychotropics. The percentages with dispensed prescription medication among the population controls were considerably lower, in particular the dispensing of psychotropics. Conclusion Dispensing of prescription medications, including psychotropic medications, is common prior to suicide. The percentage with dispensed prescription medication increases with age and are higher for females than for males.